Collaborate or Compete? Time-Varying Incentives versus Tolling in Parallel Bottleneck - Lin Xiao; Jiyan Wu; Xiangwang Hu; Jian Sun; Ye Tian (Journal of Advanced Transportation)
Incentive-based traffic demand management (IBTDM) schemes redistribute traffic demand across space and time. The relationship between IBTDM and traditional tolling programs impacts financial sustainability and decision making of both programs. This study aims to examine if an IBTDM and a tolling program can coexist and should collaborate or compete to establish a financially sustainable mobility ecosystem. We investigate a duopoly case with an IBTDM and a tolling program in a parallel bottleneck model with fixed demand. It is assumed that the IBTDM program has a user acquisition cost and is constrained by a total budget. Then, the collaboration and competition cases between two programs are investigated, respectively. We found that both programs can attract substantial amounts of commuters and thus can coexist with each other, while the IBTDM program could attract more commuters. Overall, the tolling agency will not cooperate with the IBTDM company if its goal is to raise revenue. Additionally, the IBTDM company held an advantage as it can determine an optimal incentive scheme with incomplete information when competing. This study fills the knowledge gap on the coexistence of incentive and tolling programs, which helps to optimize the profiles of incentive and tolling, as well as to make strategic decisions on competition and cooperation.